Penggunaan Metode Discovery Learning Pada Pembelajaran PAI Untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP Negeri 10 Seluma - Aliasmin, Aliasmin (Yayasan Darusssalam Bengkulu, 2020)
The objective of this study aimed at developing learning methods in teaching PAI subject at secondary school level. The research method used is classroom action research, which is carried out in II sycle which consist of four steps. The subject of the reaseach was the students of the first year at SMPN 10 Seluma Regency. Based on the results, the data shows there was improvement on the students’ achievement in understanding the goal of teaching related to the given topics. The data indicated that in each sycle increased significantly from 62% at first cycle become 85% at the secondary sycle. Then the data also show that there was improvement on students’attitude, motivation during the class activity. In conclusion, discovery learning method is effective used at SMPN 10 Seluma.